Hispanic leadership fostering parental engagement in a community-based space. Issue 3 (4th May 2019) - Gil, Elizabeth
Abstract: This case study based on data from a larger study seeks to explore how aspects of a 'communities of parental engagement' model and Hispanic leadership forms are present in a community-based program aimed at teaching basic technology skills to Hispanic immigrant adult family members. The program's culturally relevant methodology emphasised care, respect and membership, leading to parents' increased sense of efficacy and greater capacity for supporting their children's schooling. The community-based program's founder/coordinator exhibited leadership features found in Hispanic principals, influences of identity and leadership as advocacy. This case can serve as an example for educational leaders to enact culturally responsive leadership and family engagement practices and to view schools as communities rather than only as institutions.